The Use of Natural Insecticides in the Control of The Aedes Aegypti Mosquito - Pariyasi Pariyasi; Abdul Razak (Pascasarjana, Universitas Negeri Padang, 2022)
One of the problems that are closely related to the community is the case of dengue fever and the use of synthetic insecticides, which cause environmental, insect resistance, and health losses for the community. To reduce the use of synthetic insecticides, this research focuses on the use of natural insecticides in controlling the Aedes Aegypti mosquito. The method in this study is true experiment research using a completely randomized design with 6 treatments 4 repetitions with 1 aqua dest control. Natural insecticides are made from Lemongrass and eco enzymes, then sprayed onto Aedes Aegypti mosquitoes in each cage containing 10 mosquitoes, the total mosquitoes tested were 280 adult mosquitoes. The purpose of this study was to formulate a natural insecticide that is effective in killing the Aedes Aegypti mosquito and to analyze the public's acceptance of the natural insecticide made. The results showed that the 4th treatment, namely 2:1 (citronella: eco enzymes) had the highest killing power with a mortality rate of 92.5% with an average time of killing mosquitoes of 1 minute. More than 50% of the survey of 20 respondents accepted or liked natural insecticides made from aspects of color appearance, ease of use, availability of materials, and the desire to use natural insecticides, while the smell of natural insecticides, people did not accept because the smell was quite strong.